La Patrie / Our Canada: Canadian Orchestral Music 1874-1943 – Symphonova Orchestra; and Calling: John Beckwith Instrumental Works 2006-2016 (CD Reviews) - Stephen, J. Drew (CAML Review / Revue de l’ACBM, 2019)
[no abstract]